2021
DOI: 10.1007/s11307-021-01646-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of [18F]F-DPA with [18F]DPA-714 and [11C]PBR28 for Neuroinflammation Imaging in the same Alzheimer’s Disease Model Mice and Healthy Controls

Abstract: Purpose In this study we compared the recently developed TSPO tracer [18F]F-DPA, with [18F]DPA-714 and [11C]PBR28 by performing in vivo PET imaging on the same Alzheimer’s disease mouse model APP/PS1-21 (TG) and wild-type (WT) mice with all three radiotracers. Procedures To compare the radiotracer uptake, percentage of injected dose/mL (%ID/mL), standardized uptake value ratios to cerebellum (SUVRCB), and voxel-wise analyses were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In our study, we used the APP/PS1-21 transgenic (TG) mouse model of Aβ deposition, a reliable model to validate radiotracers in preclinical settings, which has been used in the development of novel PET radiotracers targeting reactive glia [ 26 , 27 ] and misfolded proteins, such as tau [ 28 ]. In this model, early onset Aβ plaques are associated with simultaneous and robust neuroinflammation, represented by the presence of increased reactive microglia around the Aβ plaques [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we used the APP/PS1-21 transgenic (TG) mouse model of Aβ deposition, a reliable model to validate radiotracers in preclinical settings, which has been used in the development of novel PET radiotracers targeting reactive glia [ 26 , 27 ] and misfolded proteins, such as tau [ 28 ]. In this model, early onset Aβ plaques are associated with simultaneous and robust neuroinflammation, represented by the presence of increased reactive microglia around the Aβ plaques [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to image reactive glia in the APP/PS1-21 TG mouse model of Aβ deposition longitudinally with [ 11 C]SMW139 targeting P2X7 receptor and compare tracer uptake in the same mice to that of [ 18 F]F-DPA targeting TSPO at the final imaging time point. In previous studies, [ 18 F]F-DPA targeting TSPO in the APP/PS1-21 mouse model has shown the ability to image reactive glia, differentiate transgenic from age-matched wild type mice, and superior brain uptake to the TSPO PET tracers [ 18 F]DPA-714 and [ 11 C] PBR28 [ 30 , 31 ]. This study contributes to the development of [ 11 C]SMW139 and [ 18 F]F-DPA for imaging reactive glia in the APP/PS1-21 mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…The 18-kDa translocator protein (TSPO)-binding radiotracers are the most widely used radiopharmaceuticals for imaging neuroinflammation; [ 11 C]­PK11195 PET has been used to evaluate microglial response in fingolimod-treated MS patients . Its poor signal-to-noise ratio, high lipophilicity, and low blood–brain barrier penetration prevent the implementation of [ 11 C]­PK11195 on clinical practice. , Consequently, a few second-generation PET radiotracers, such as [ 11 C]­PBR28, [ 18 F]­GE180, [ 18 F]­DPA-714, and [ 18 F]­F-DPA for imaging TSPO, have been reported. Nevertheless, the Ala147Thr genotype polymorphism of TSPO influences the brain uptake of most of the TSPO radiotracers, resulting in the need for genetic prescreening to prevent high within-group variation, which creates substantial complexity for clinical studies. S1PR1 has gained significant interest since the approval of the S1PR modulators for the treatment of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the presence of the rs6971 single nucleotide polymorphism (SNP) in TSPO , which produces different radioligand binding affinities (Owen et al, 2011 ; Tournier et al, 2020 ). Currently, TSPO is the primary target for PET and SPECT in vivo neuroinflammatory imaging to monitor the inflammatory state in the brain (Tournier et al, 2020 ; López-Picón et al, 2022 ). According to one of the hypotheses of AD pathogenesis, mitochondrial dysfunction occurs in the early stages, and thus, maintaining mitochondrial function may be a therapeutic strategy for AD (Readnower et al, 2011 ; Eckert et al, 2012 ; Kumar A. et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%